2005
DOI: 10.2320/matertrans.46.2380
|View full text |Cite
|
Sign up to set email alerts
|

Joints Soldered on Electroless Ni–Au Surfaces Using Cu-Containing Flux: Strength, Microstructure and Mechanism of Improvement

Abstract: The critical issue for soldering on electroless Ni-Au surface finishes is fragile solder joints. Previous studies have indicated that these weak joints are a result of the formation of a P-rich layer at the joint interface. In this study, the new flux, which contains a Cu compound, demonstrates improved solder joint strength for solder ball attachment on electroless Ni-Au surface finishes. Cross-sectional analysis revealed that this new flux gives a thinner P-rich layer at the joint interface than that seen wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…As a way to decrease the growth of a P-rich layer, the authors of this current study previously reported that the use of a flux containing 10 wt.% of Cu(II) stearate could suppress Ni diffusion in a Sn-based solder on an ENIG surface finish [9][10][11]. Due to their tendency to ionize, Cu ions derived from Cu(II) stearate would be reduced through a substitution reaction with Ni, as described by Eq.…”
Section: Introductionmentioning
confidence: 93%
“…As a way to decrease the growth of a P-rich layer, the authors of this current study previously reported that the use of a flux containing 10 wt.% of Cu(II) stearate could suppress Ni diffusion in a Sn-based solder on an ENIG surface finish [9][10][11]. Due to their tendency to ionize, Cu ions derived from Cu(II) stearate would be reduced through a substitution reaction with Ni, as described by Eq.…”
Section: Introductionmentioning
confidence: 93%
“…18 In this case, the substitution reaction between Ni and Cu, as described in Eq. 1, is utilized in forming a Cu layer that serves as a temporal barrier on the Ni-P plating.…”
Section: Introductionmentioning
confidence: 99%
“…18 Because of the presence of a Cu resource near the joint interface, a flux that contains Cu(II) stearate, known as barrier flux, is believed to form an effective Cu barrier layer before the solder melts on the conventional electroless Ni-P surface finish. This Cu layer contributes to the suppression of excess diffusion of Ni into the solder, and hence the formation of a P-rich layer at the joint interface is reduced.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to resolve this, the present authors applied the notable barrier function of Cu to the property of flux used for the BGA solder ball attachment on electroless Ni-plated surface finish in our previous studies. [17][18][19] The addition of the Cu compound, copper(II) stearate, to the flux controlled the growth of both intermetallic compounds and the P-rich layer at the joint interface in several soldering systems, such as those using Sn-Pb, Sn-Ag, and Sn-Ag-Cu. Observation of the microstructure revealed that refined intermetallics, as well as a thin P-rich layer, were formed at the joint interface when using the flux containing the Cu compound.…”
Section: Introductionmentioning
confidence: 99%